A theory of autocratic transition: Prerequisites to self-enforcing democracy - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2018)
This paper aims at contributing to a better understanding of the conditions of self-enforcing democracy by analyzing the recent wave of autocratic transitions. Based on a game-theoretic framework, we work out the conditions under which governments may induce the diverse public authorities to coordinate on extra-constitutional activities, eventually transforming the politico-institutional setting into one of autocratic rule. We find three empirically testable characteristics that promote this coordination process, namely: populism and public support, corruption, and a lack in the separation of powers. By contrast, low degrees of corruption and strongly separated powers can be viewed as prerequisites to self-enforcing democracy.
Keywords: D02; D72; D74; P48; 330